Duplex real-time pcr using sybr green i for quantification and differential diagnosis between salmonella enteritidis and salmonella typhimurium - Rubio, M. S. [UNESP]; Penha Filho, Rafael Antonio Casarin [UNESP]; Almeida, A. M. [UNESP]; Barbosa, F. O. [UNESP]; Berchieri, A. [UNESP] (FapUNIFESP (SciELO), 2019)
The incidence of foodborne diseases caused by the genus Salmonella spp. in industrialized countries is often high in epidemiological surveys. Obtaining a rapid diagnostic test for identification of bacteria is crucial in order to rapidly implement control measures to contain bacterial spread, to reduce losses in animal production and to avoid risks from food-borne infections to human health. The aim of this study was to standardize duplex real-time PCR using SYBr Green I for differential and quantitative diagnosis of S. Typhimurium and S. Enteritidis. According to the experiment, the melting temperature of 85°C was observed for a 206bp amplified product when S. Enteritidis DNA was added to the reaction. S. Typhimurium DNA showed that the melting temperature of 79°C when observed for a 62bp amplified product. The standard curve showed the high sensitivity of the proposed test, since it was possible to obtain eight quantification points, starting at 108 CFU/mL and ending at 101 CFU/mL. As a result of the present study, a real-time PCR duplex reaction with high sensitivity, specificity and based on the fluorescence of SYBr Green I was standardized. In addition, this methodology aligns low cost to the faster diagnostic result, in relation to other molecular tests, making it attractive for application in routine laboratory analyzes.
Keywords: Identification; Melting curve; Non-typhoidal salmonellosis; Standard curve